Infectious Pulmonary Artery Pseudoaneurysm That Resolved with Conservative Treatment - Nakayama, Toshihiro; Suzuki, Manabu; Yamaguchi, Yoh; Iikura, Motoyasu; Izumi, Shinyu; Takeda, Yuichiro; Hojo, Masayuki; Sugiyama, Haruhito (Internal Medicine, 2022)
Pulmonary artery pseudoaneurysms (PAPs) are rare but can cause massive hemoptysis if they rupture. Infectious PAPs are often treated by surgery or transcatheter embolization and are rarely treated conservatively with antibiotics. We herein report a case of PAP treated conservatively in a 21-year-old woman with lung abscess. Except for one massive hemoptysis early in the course, the patient responded well to the empirical therapy with ampicillin/sulbactam and systemic hemostatic agents. After six weeks of antibiotics, the pseudoaneurysm disappeared. Conservative therapy with careful observation can be considered in small infectious PAPs when there is a good clinical response to initial conservative therapy.